Color thresholding method for image segmentation algorithm of Ziehl-Neelsen sputum slide images - Rafikha Aliana, A. Raof (Institute of Electrical and Electronics Engineers (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org